2012
DOI: 10.1007/s00285-012-0512-2
|View full text |Cite|
|
Sign up to set email alerts
|

Optimal solution for a cancer radiotherapy problem

Abstract: We address the problem of finding the optimal radiotherapy fractionation scheme, representing the response to radiation of tumour and normal tissues by the LQ model including exponential repopulation and sublethal damage due to incomplete repair. We formulate the nonlinear programming problem of maximizing the overall tumour damage, while keeping the damages to the late and early responding normal tissues within a given admissible level. The optimum is searched over a single week of treatment and its possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…Previous reports have independently modeled the effect of either fixed or dynamic fractionation schemes (Brenner et al 1998;Lu et al 2008), the effect of incomplete DNA damage repair (Bertuzzi et al 2013), the impact of the 4R's and tumor proliferation (Yang and Xing 2005), and the impact of hyper-or hypo-fractionated schedules (Unkelbach et al 2013;Mizuta et al 2012). Dionysiou et al (2004) further examined hyper-fractionating using a novel fourdimensional simulation model of GBM and observed an increased tumor reduction when compared to standard fractionation.…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports have independently modeled the effect of either fixed or dynamic fractionation schemes (Brenner et al 1998;Lu et al 2008), the effect of incomplete DNA damage repair (Bertuzzi et al 2013), the impact of the 4R's and tumor proliferation (Yang and Xing 2005), and the impact of hyper-or hypo-fractionated schedules (Unkelbach et al 2013;Mizuta et al 2012). Dionysiou et al (2004) further examined hyper-fractionating using a novel fourdimensional simulation model of GBM and observed an increased tumor reduction when compared to standard fractionation.…”
Section: Introductionmentioning
confidence: 98%
“…Other authors have considered extensions to incorporate effects from repopulation, the overall treatment time, and incomplete repair. [6][7][8] The projected benefit of delivering different dose distributions in different fractions has been studied for a stylized proof-of-concept model in Ref. 9, and the idea was conceptually introduced in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that time dependencies in tumor growth and radiation response, such as accelerated repopulation and incomplete repair, may give rise to nonuniform fractionation schemes. 8,9 In this paper, we consider the standard BED model. It is therefore interesting to note that the simultaneous optimization of fractionation schemes leads to nonuniform fractionation schemes that deliver distinct dose distributions in different fractions-even in the absence of any time dependencies in the BED model.…”
Section: E Further Remarksmentioning
confidence: 99%
“…Other authors have considered extensions of the BED model to incorporate effects from repopulation, the overall treatment time, and incomplete repair. 8,9 In this paper, we consider the extension of BED-based fractionation to the fluence map optimization context. In other words, we consider the simultaneous optimization of the fluence map and the fractionation scheme.…”
Section: Introductionmentioning
confidence: 99%